Effects of high-fat diet on antioxidative status, apoptosis and inflammation in liver of tilapia (Oreochromis niloticus) via Nrf2, TLRs and JNK pathways. Issue 104 (September 2020) - Jia, Rui; Cao, Li-Ping; Du, Jin-Liang; He, Qin; Gu, Zheng-Yan; Jeney, Galina; Xu, Pao; Yin, Guo-Jun
Abstract: Fatty liver injury (or disease) is a common disease in farmed fish, but its pathogenic mechanism is not fully understood. Therefore the present study aims to investigate high-fat diet (HFD)-induced liver injury and explore the underlying mechanism in fish. The tilapia were fed on control diet and HFD for 90 days, and then the blood and liver tissues were collected to determine biochemical parameter, gene expression and protein level. The results showed that HFD feeding signally increased the levels of plasma aminotransferases and pro-inflammatory factors after 60 days. In liver and plasma, HFD feeding significantly suppressed antioxidant ability, but enhanced lipid peroxidation formation, protein oxidation and DNA damage after 60 or 90 days. Further, the Nrf2 pathway and antioxidative function-related genes were adversely changed in liver of HFD-fed tilapia after 60 and/or 90 days. Meanwhile, HFD treatment induced apoptosis via initiating mitochondrial pathway in liver after 90 days. Furthermore, after 90 days of feeding, the expression of genes or proteins related to JNK pathway and TLRs-Myd88-NF-κB pathway was clearly upregulated in HFD treatment. Similarly, the mRNA levels of inflammatory factors including tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), IL-6, IL-8 and IL-10 were also upregulated in liver of HFD-fed tilapia after 60 and/or 90 days. In conclusion, the current study suggested that HFD feeding impaired antioxidant defense system, induced apoptosis, enhanced inflammation and led to liver injury. The adverse influences of HFD in the liver might be due to the variation of Nrf2, JNK and TLRs-Myd88-NF-κB signaling pathways. Highlights: HFD feeding impairs Nrf2 pathway to weaken antioxidant defense system in liver of tilapia. HFD feeding induces apoptosis via mitochondrial pathway. HFD feeding activates JNK-NF-κB pathway and TLRs-MyD88-NF-κB pathway to mediate inflammatory response.